Mechanism of complement activation in the hyperacute rejection of porcine organs transplanted into primate recipients. - Dalmasso, A. P. (1992)
The authors investigated the importance of natural antibody and complement in the pathogenesis of hyperacute xenograft rejection using in vivo and in vitro pig to primate models. Studies were carried out in rhesus monkeys transplanted with a pig heart or kidney in which hyperacute rejection was observed within a few hours. The rejected organs showed deposits of IgM, C3, C4, C5, and C9 neoantigen along small blood vessels, but few deposits of factors B and P. Removal of anti-endothelial cell "natural" antibodies by plasmapheresis, immunoabsorption, and immunosuppression techniques resulted in marked prolongation of the survival of a subsequently transplanted heart, even when complement levels were within the normal range. Thus, complement, in the absence of natural antibodies, did not initiate hyperacute rejection in this species combination. The requirements for complement activation in human serum to cause cytotoxicity of porcine endothelial cells were then evaluated. Cytotoxicity was abrogated by depleting human serum of IgM, C2, or C5, but not of factor B. Restoration of the effect of serum on endothelial cells was achieved by reconstitution of the respective depleted sera with purified IgM or with the corresponding complement proteins, indicating that IgM and the classical, but not the alternative, pathway of complement, were involved. Identical conclusions were drawn from experiments to ascertain the requirements for complement activation in human serum to mediate binding of iC3b to porcine endothelial cells. The authors conclude that in a pig to primate xenograft complement does not directly initiate injury to the graft but rather requires activation by bound xenoreactive natural antibodies; IgM antibodies directed against endothelial cells activate the classical complement pathway, which then contributes to endothelial cell activation and subsequent events characteristic of hyperacute rejection.